#TITLE_ALTERNATIVE# - NARESWARI PAWITRA (NIM. 15108062); pembimbing : Dr. Deni Suwardhi, ST., MT ; Dr. Akhmad Riqq, DWITYA
Orthophoto is a photo that has undergone rectification process aimed at eliminating the effects of relief displacement, so that the resulting image looks like having an orthogonal projection. Accuracy of the position and geometry of the given object from the orthophoto is an important aspect in making spatial information, especially the modeling of three-dimensional (3D) structure. Other than orthophoto, there is also true orthophoto which is able to represent an object by calculating the geometry more accurately. The process of making true orthophoto must go through the process of differential rectification consisting of the collinear relationship (collinearity) and pixel manipulation. In this study, true orthophoto which is usually produced from aerial photographs is applied to close range or terrestrial photogrammetry. True orthophoto is reconstructed for each facade of the building, and generated true orthophoto is used as texture image and attached to the 3D model building to make the models look more realistic. This research was conducted to develop a simple algorithm of true orthophoto creation because most of the current software does not explain the mechanism of the software process (blackbox). In addition, the case study for this research consists three objects, which are a simple box, aerial photographs that covered north area from ITB Campus, and simple security pos near GKU Barat Building in ITB Campus. Each object is modeled and divided into several building facade, then generated orthophoto from one of the facades with MATLAB software and compared with the result from PhotoModeler Scanner. The result of each object has different precision quality. The qualities of orthophotos are influenced by model and camera quality. The result of each object has different precision quality. The quality of orthophotos are influenced by model and camera quality.